ANTECEDENTS OF STORE LOYALTY: THE CASE OF GOVERNMENT-OWNED SUPER MARKETS IN KERALA - Dr. George A.P and Yamuna Govinda (International Journal of Business and Administration Research Review, 2014)
This paper examines the effect of merchandise quality, service quality, store satisfaction, trust and perceived value on loyalty towards government-owned supermarkets in Kerala. The results show that the combined effect of the stated variables on store loyalty is statistically significant. Perceived value proved to be the most important predictor of store loyalty followed by Merchandise quality and Trust. Store satisfaction did not show statistical significance though the correlation value was positive. Service Quality showed negative and no statistically significant correlation. The result indicates that the government-owned supermarkets in Kerala, though appears to be meeting customer expectations in terms of merchandise quality, perceived value and trust, has to take adequate measures to improve quality of service and store satisfaction. The findings of the study highlight the importance of understanding store loyalty behavior and suggest that the supermarkets have to focus on various marketing mix elements and potential loyalty drivers to create positive loyalty and re-patronage intentions among the customers.